Prognosis of Patients With Testicular Carcinoma Is Dependent on Metastatic Site - Xu, Peihang; Wang, Jun; Abudurexiti, Mierxiati; Jin, Shengming; Wu, Junlong; Shen, Yijun; Ye, Dingwei (Frontiers in Oncology, 2020)
Background: Existing data on the association of metastatic sites and prognosis of patients with metastatic testicular malignancy are limited. In this study, the association of survival outcome and the prognostic value of different metastatic sites in patients with metastatic testicular cancer was investigated. Methods: A dataset from the Surveillance, Epidemiology and End Results (SEER) survey was selected for a retrospective metastatic testicular cancer cohort study. Patients with different metastatic sites were divided into corresponding groups for further analysis. Kaplan-Meier analysis with log-rank test was implemented for comparison of the survival distribution of cases. Multivariate Cox regression models were then applied to analyze the association of distant metastases with survival for all selected patients and subgroup based on different histological type with a single metastatic site. Results: A total of 1661 patients treated for metastatic testicular malignant tumors between 2010 to 2016 were enrolled in this cohort study. Upon initial diagnosis, 61.9%, 15.2%, 6.7%, 6.4%, and 36.2% of patients were found to have lung, liver, bone, brain, and distant lymph nodes metastatic sites, respectively. Patients with lung, liver, or bone metastases showed more undesirable prognosis for overall survival (OS) and cancer-specific survival (CSS), in contrast with those with distant lymph node metastases (all P<0.05). In comparison with patients with more than one metastatic site, those with a single metastasis had extended OS and CSS (both P<0.001). In patients with a single metastatic site, Kaplan–Meier analysis and multivariate Cox regression demonstrated the association of bone and liver with the worst two groups of OS and CSS. Multivariate Cox models based on histological type showed different prognostic values of metastases in patients with seminoma or nonseminomatous germ cell tumors. Conclusion: There is much heterogeneity in the oncological outcome of site-specific metastatic patients. Metastatic profiles and the prognostic value of metastases are dependent on the histological type in TC patients. Distant lymph nodes and lung metastases indicate favorable prognostic factors, while bone and liver metastases indicate negative survival outcomes in TC.